2020
DOI: 10.1126/sciadv.aay6994
|View full text |Cite
|
Sign up to set email alerts
|

In vivo priming of human mesenchymal stem cells with hepatocyte growth factor–engineered mesenchymal stem cells promotes therapeutic potential for cardiac repair

Abstract: The clinical use of human bone marrow–derived mesenchymal stem cells (BM-MSCs) has been hampered by their poor performance after transplantation into failing hearts. Here, to improve the therapeutic potential of BM-MSCs, we developed a strategy termed in vivo priming in which BM-MSCs are primed in vivo in myocardial infarction (MI)–induced hearts through genetically engineered hepatocyte growth factor–expressing MSCs (HGF-eMSCs) that are encapsulated within an epicardially implanted 3D cardiac patch. Primed BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 25 publications
0
69
0
1
Order By: Relevance
“…Indeed, Park et al recently suggested a brand new function improvement method called in vivo priming. In their study, the authors transduced BM-MSCs to consistently secrete HGF and the engineered cells were seeded on 3D patch mixing with naïve cells resulting in the improvement of therapeutic function compared to naive MSCs [75]. Therefore, optimization of the combinatorial use of each strategy could be envisioned to maximize the therapeutic outcome of MSC therapy.…”
Section: Future Perspectives and Concluding Remarksmentioning
confidence: 99%
“…Indeed, Park et al recently suggested a brand new function improvement method called in vivo priming. In their study, the authors transduced BM-MSCs to consistently secrete HGF and the engineered cells were seeded on 3D patch mixing with naïve cells resulting in the improvement of therapeutic function compared to naive MSCs [75]. Therefore, optimization of the combinatorial use of each strategy could be envisioned to maximize the therapeutic outcome of MSC therapy.…”
Section: Future Perspectives and Concluding Remarksmentioning
confidence: 99%
“…To achieve better treatment, various methods have been developed to extend the therapeutic potential of current MSCs ( 86 ). Primed MSCs through genetically engineered hepatocyte growth factor–expressing MSCs (HGF-eMSCs) was developed by Park et al ( 45 ), showing largely improved vasculogenic ability and enhanced cell viability. After encapsulated in a cardiac patch, this kind of MSCs promoted vascular regeneration and repaired cardiac function within MI hearts.…”
Section: Cell Sourcesmentioning
confidence: 99%
“…MSCs facilitate neurological recovery and neo-angiogenesis through the secretion of neurotrophins and angiogenesis regulatory factors [8][9][10]. The ability of immunomodulatory effect, migratory capability, and regenerative potential of MSCs are confirmed in multiple disease models, such as atopic dermatitis, myocardial infarction, traumatic brain injury, and diabetes nephropathy [11][12][13][14]. However, accumulating researches suggest that the biodistribution of MSCs in the target organs is rare, and its therapeutic effect appears to be a consequence of the paracrine action [15][16][17].…”
Section: Introductionmentioning
confidence: 99%